Effect of polypropylene fiber on the flexural strength of ferrocement - Usman F.; Shaharudin S.; Abd Ghani M.F. (Trans Tech Publications Ltd, 2023)
This paper presents the effect of Polypropylene Fiber (PPF) on the flexural strength of ferrocement. Various percentage of PPF content which are 0%, 1.0%, 1.5% were added into mortar matrix during preparing of ferrocement specimens. For each percentage of PPF, three specimen of ferrocement were produced. Each specimen were reinforced with different number of steel wire mesh layers which are 2 layers, 4 layers and 6 layers. Each specimens were tested under 3-point loading to obtain its flexural strength. It is observed that optimal percentage of PPF adding into mortar matrix will improve the flexural strength when it is in a range of 1% to 1.5%. © (2014) Trans Tech Publications, Switzerland.